A new model of information behaviour based on the Search Situation Transition schema Information searching, Information behaviour, Behavior, Information retrieval, Information seeking - Nils Pharo (Information Research: An International Electronic Journal)
This paper presents a conceptual model of information behaviour. The model is part of the Search Situation Transition method schema. The method schema is developed to discover and analyse interplay between phenomena traditionally analysed as factors influencing either information retrieval or information seeking. In this paper the focus is on the model's five main categories: the work task, the searcher, the social/organisational environment, the search task, and the search process. In particular, the search process and its sub-categories search situation and transition and the relationship between these are discussed. To justify the method schema an empirical study was designed according to the schema's specifications. In the paper a subset of the study is presented analysing the effects of work tasks on Web information searching. Findings from this small-scale study indicate a strong relationship between the work task goal and the level of relevance used for judging resources during search processes.